p62 filaments capture and present ubiquitinated cargos for autophagy - Zaffagnini, G; Savova, A; Danieli, A; Romanov, J; Tremel, S; Ebner, M; Peterbauer, T; Sztacho, M; Trapannone, R; Tarafder, AK; Sachse, C; Martens, S (EMBO Press, 2018)
The removal of misfolded, ubiquitinated proteins is an essential part of the protein quality control. The ubiquitin‐proteasome system (UPS) and autophagy are two interconnected pathways that mediate the degradation of such proteins. During autophagy, ubiquitinated proteins are clustered in a p62‐dependent manner and are subsequently engulfed by autophagosomes. However, the nature of the protein substrates targeted for autophagy is unclear. Here, we developed a reconstituted system using purified components and show that p62 and ubiquitinated proteins spontaneously coalesce into larger clusters. Efficient cluster formation requires substrates modified with at least two ubiquitin chains longer than three moieties and is based on p62 filaments cross‐linked by the substrates. The reaction is inhibited by free ubiquitin, K48‐, and K63‐linked ubiquitin chains, as well as by the autophagosomal marker LC3B, suggesting a tight cross talk with general proteostasis and autophagosome formation. Our study provides mechanistic insights on how substrates are channeled into autophagy.